Differences in the peptide profile of raw and pasteurised ovine milk cheese and implications for its bioactive potential. (March 2015) - Pisanu, Salvatore; Pagnozzi, Daniela; Pes, Massimo; Pirisi, Antonio; Roggio, Tonina; Uzzau, Sergio; Addis, Maria Filippa
Abstract: Cheese produced using raw ovine milk (R) or pasteurised ovine milk (P) was subjected to peptide extraction, characterisation by mass spectrometry and bioinformatic analysis with the aim of assessing the impact of milk pasteurisation on the final peptide profile. In total, 187 peptides arising from β-casein, αS1 -casein, and αS2 -casein were identified. Upon label-free quantitation, 58 peptides were found to be significantly different in the two preparations; 38 were more abundant in R and 20 were more abundant in P. Of these, 27 were unique to R and 10 were unique to P. Bioinformatic analysis by EnzymePredictor provided insights into the influence of milk pasteurisation on susceptibility of cheese proteins to proteolytic enzymes during ripening. Finally, BIOPEP analysis predicted a biological activity for 37 of the 187 identified sequences (20%), with a significantly higher abundance of peptides with immunomodulating and ACE-inhibitor properties in R cheeses.